A textbook of human anatomy - Crafts, Roger C. (Wiley, 1985)
The format of this updated third edition does not depart greatly from that used in the first and second editions. General descriptions of each region have been followed by more detailed presentations of the structures in the same region. The description of each major area of the body ends with a systemic summary of that area. Clinical correlation has been increased but no attempt has been made to create a clinical or surgical text. A judicious amount of such material has been added, particularly when such a description would aid in learning the anatomy. Moreover, the chapters on the limbs have been rearranged to fit clinical thinking.